Level of awareness on the legal implications of plagiarism among adult learners: a case study of public and private universities in Johor and Melaka - Ali, Alizah; Jangga, Rohani; Mohd Basir, Nora (2012)
Plagiarism is a serious academic dishonesty that shall be banned by universities. Nowadays, adult learner who has constrained of time prefers to copy and paste from internet and declared as their opinion. This study is to investigate the level of awareness as well as the level of legal awareness of plagiarism among adult learners especially those who distance from the institutions. In order to accomplish the objectives, we use Regression which include Pearson's correlation, coefficient and model summary that stress on R square value. From the result, we can conclude that plagiarism activity is high among adult learner and they do not aware on committing plagiarism while doing their assignment. We also find that these student do not aware the legal implication from such academic dishonesty.